2018
DOI: 10.1038/s41598-018-31424-3
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of human IgG recognition within the Staphylococcus aureus immunome

Abstract: Staphylococcus aureus is an opportunistic pathogen that causes a range of serious infections associated with significant morbidity, by strains increasingly resistant to antibiotics. However, to date all candidate vaccines have failed to induce protective immune responses in humans. We need a more comprehensive understanding of the antigenic targets important in the context of human infection. To investigate infection-associated immune responses, patients were sampled at initial presentation and during convales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Among the panoply of exotoxins released during S. aureus infection, we chose the leukocidin family for our proof-of-principle study, in part because several of the members have been reported to be direct contributors to clinical syndromes of invasive and potentially life-threatening infections (40,41,45). In addition, our experimental design exploited the extensive literature on the shared structural features of Luk toxin subunits (46)(47)(48)(49), which are integral to their properties as efficient molecular killing machines through formation of pores that cause host cell toxicity and death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the panoply of exotoxins released during S. aureus infection, we chose the leukocidin family for our proof-of-principle study, in part because several of the members have been reported to be direct contributors to clinical syndromes of invasive and potentially life-threatening infections (40,41,45). In addition, our experimental design exploited the extensive literature on the shared structural features of Luk toxin subunits (46)(47)(48)(49), which are integral to their properties as efficient molecular killing machines through formation of pores that cause host cell toxicity and death.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we document here an approach that enabled the identification by a monoclonal antibody of a minimal epitope recapitulated in a small linear synthetic peptide that also displayed the immunogenicity of the native toxin. It is important to consider that immunodominant leukocidin epitopes recognized after murine immunization may be different in humans, who from an early age are commonly colonized and later suffer recurrent, although often minor, infections that induce circulating antibodies and memory B cells against many S. aureus antigens (40,41). Indeed, although lasting postinfection enhancement of protection is uncommon or at best unpredictable (40), members of the Luk family are high on the hierarchy of protein antigens recognized by the immune responses of adults and children recovering from S. aureus infection (41,45,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite many attempts, all efforts to develop an efficacious protective S. aureus vaccine have failed to meet their primary endpoints in clinical trials. At the same time, adults commonly have circulating IgG antibodies (Abs) to hundreds of S. aureus proteins with high reactivity for exotoxins that include the members of the bicomponent pore-forming toxin (PFT) family (9), and memory B-cell responses to PFT members are also common in both healthy adults and those recovering from S. aureus infection (3). These memory responses include antibodies with cross-reactivity between structurally related PFT subunits (3).…”
mentioning
confidence: 99%
“…For example, the Panton-Valentin leukocidin (LukSF-PV) is associated with primary skin and soft tissue infection and pneumonia (15). Although these factors represent important antigens recognized by host immunity (3,9), sites within such toxins have been assigned defined functional roles in pathogenesis in only a few cases, such as for the recognition of target cells or at the interface of the assembled toxin subunits required for pore formation (reviewed in reference 11).…”
mentioning
confidence: 99%